2015
DOI: 10.1097/gox.0000000000000366
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Cavity or Alveolar Paranasal Sinus Rhabdomyosarcoma with Orbital Extension in Adults

Abstract: Summary:Alveolar rhabdomyosarcoma (RMS) has a predilection for the deep soft tissues of the extremities and mainly occurs in children. Although the tumor may originate in other sites, such as the nasal cavity or paranasal sinus, invasion of the orbit is unusual. We describe the clinicopathological features of 2 cases of alveolar RMS of the nasal cavity or paranasal sinus in adult patients with orbital extension. These cases of alveolar RMS of the nasal cavity or paranasal sinuses are described in 2 men, both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Moon et al, described a patient with alveolar RMS of the ethmoid sinus with extending to the orbit and cervical lymph node involvement, who was treated with surgery and chemoradiotherapy, but died after seven months because of metastasis that progressed to the spine [2]. Similarly, Torres-Peña et al, described two adults with alveolar RMS, one patient showed the involvement of ethmoid sinus and right orbit; in the other patient the mass was centered at the nasal cavity and infiltrated the orbit and the ethmoidal and frontal sinuses [3]. Both of the patients died because of systemic complications associated with the invasion, after two above, where non-metastatic RMS is associated with no recurrence, our case is markedly different because our patient experienced recurrence, but did not have metastatic disease [Table /Fig-3].…”
Section: Discussionmentioning
confidence: 99%
“…Moon et al, described a patient with alveolar RMS of the ethmoid sinus with extending to the orbit and cervical lymph node involvement, who was treated with surgery and chemoradiotherapy, but died after seven months because of metastasis that progressed to the spine [2]. Similarly, Torres-Peña et al, described two adults with alveolar RMS, one patient showed the involvement of ethmoid sinus and right orbit; in the other patient the mass was centered at the nasal cavity and infiltrated the orbit and the ethmoidal and frontal sinuses [3]. Both of the patients died because of systemic complications associated with the invasion, after two above, where non-metastatic RMS is associated with no recurrence, our case is markedly different because our patient experienced recurrence, but did not have metastatic disease [Table /Fig-3].…”
Section: Discussionmentioning
confidence: 99%
“…Turner et al in a population studyof incidence and survival in head and neck RMS reported an annual percentage increase of 1.16% and a statistically un-changed 5-year survival over the past 30years despite advances in treatment modalities; all this data against other studies with reports of improved survival. 3,7 Relative survival (RS) was more dependent on the extent of disease than primary site, and it was noted that most orbital RMS tumors (60.6%) presented with localized disease and, consequently, had a 5-year survival of about 84.3% which is more promising when compared with other sites in the head and neck. …”
Section: Introductionmentioning
confidence: 91%
“…1, 2 Most of these tumors presents in the first decade of life 3 , but RMS has been reported from birth to the eighth decade. 1,4,5 The incidence of malignant orbital tumors in general has been increasing in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…Case reports of adults with orbital extension of RMS have been reported to cause vision loss as in this case; however, most of these patients are in young adulthood. 3,4 To our knowledge, this patient is the oldest to present with significant and permanent vision loss from RMS; one report exists of a case of a 68-year-old woman with mild vision loss that resolved with treatment. 5 This patient's original presenting symptoms of unilateral headache and nasal congestion were typical for sinusitis, a common differential diagnosis among patients with sinus-involving RMS.…”
mentioning
confidence: 94%
“…In conjunction with the IVFA performed 2 months ear- Letters to the Editor 831 lier, these findings were consistent with delayed reperfusion following tumour regression with treatment. 3,4 However, further workup should be initiated in the setting of vision changes or proptosis. 2 It originates from immature mesenchymal cells that normally differentiate into skeletal muscle.…”
mentioning
confidence: 99%